The Role of Tax Consultants Against Taxpayers in Indonesia To Be Aware of Paying Tax - Sugiharto; Iwan Suhasto; Koerniawan Wibawa; Mashitoh (Politeknik Negeri Madiun, 2023)
To find out the level of awareness of taxpayers in paying taxes and analyze the role of tax consultants on awareness of taxpayers towards fulfilling the obligation to pay taxes. Quantitative research methods with data analysis techniques are descriptive and quantitative. The analysis model used is multiple regression analysis, processed using the SPSS version 17 application. The variables of awareness of paying taxes, tax regulations, and tax fund misappropriation do not affect the tax consultant. The presence of a tax consultant cannot guarantee that taxpayers are aware of their tax obligations. Meanwhile, the variable understanding of taxation, potential tax objects, and tax benefits influences tax consultants. Tax consultants provide understanding to taxpayers to know and understand tax regulations such as the amount of tax payable, the maximum tax deposit limit, and the maximum tax reporting limit.